Migrated Implant Causing Refractory Headache in Rhinoplasty - Tseng, Wen Hsuan; Chiu, Yu-Hsun Tony (Facial Plastic Surgery, 2016)
Alloplastic materials are popular and readily available for use in nasal augmentations. Among them, silicone implant is one of the most widely used, especially in certain areas in Asia for its reasonable cost and relatively simple operative technique. A major disadvantage of silicone is its notorious mobility after implantation and rate of extrusion if traumatized or exposed. Here, an unusual complication of a silicone implant for rhinoplasty was presented. We report a case of a 58-year-old woman who had augmentation rhinoplasty 20 years ago suffered from headache for over a year. Brain lesion and neurologic causes were ruled out by neurologists and physician in family medicine. Local finding showed upwardly deviated nasion and vague shape of silicone implant underneath the skin on nasal dorsum.
Keywords: headache; rhinoplasty; augmentation rhinoplasty; silicone implant; alloplastic material